The effect of low or high income on the physical growth of eighteen one to three-year old children living in a slum area in Cubao, Metro Manila. - Pecson, Anita C.
Malnutrition is a public health problem in developing countries such as the Philippines. The preschool children particularly those in the 1 to 3-year age group are the most vulnerable to malnutrition. Investigations show that malnutrition during this period of rapid growth and development prevent an individual from attaining optimum physical growth. There are several factors influencing the physical growth of children and one of the most important is the socio-economic aspect. This study was conducted to determine the effect of low or high income level on the growth of children in an urban slum community. The experiments were conducted in Cubao, Metro Manila for a period of 4 months. The objective was determine whether children in the area but coming from different income levels had similar growth rates. Annual income, monthly per capital income and indirect income indicators' score were employed to classify families into high or low income level. Height and weight measurements and dietary intakes obtained by the 24-hour recall method were studied. The matching technique was used for selecting 9 pairs (18 pre-schoolers) for this study. Each subject chosen from the high income group was matched with 1 from the low income group according to age, sex, number of siblings, and the ages of their mothers and siblings. The results showed that the children in the high income group had greater mean heights and weights, better nutritional status, and higher percent adequacies for energy, protein, iron, and Vitamin A compared with their coevals fom the low income group. The adequacies for energy in the diets of both groups were significantly decreased when illnesses took place about 1 to 2 weeks prior to the dietary recordings. The observed physical growth rates of the children in the high income level were slightly greater compared with their counterparts in the low income group. However, the observed differences were not significant and might have been accounted for by the short period of the study, small sample size, and low classification of income used for the high income group.